Yersinochloa nianheana (Poaceae, Bambusoideae), a new species from southern Vietnam - Nông, Văn Duy (PENSOFT, 2024)
Yersinochloa nianheana sp. nov. from Vietnam is described and illustrated. It is found in southern Vietnam, where it occurs at an elevation of 1400–1500 m in Voi Mountain, Duc Trong District, Lam Dong Province. This new species is distinguished from a similar species, Yersinochloa dalatensis, by culm nodes with a thick swollen patella, culm leaf blades erect, auricles conspicuous, margins bearing long hairs, palea dorsal view showing rachilla extension and rudimentary floret at the apex and lodicules purple gradually towards the top. Besides that, the species is distinguished from Yersinochloa nghiana by the leaf blades without being swollen at the base, the prophyllate bud 2-keeled, lodicules purple at ½ upper parts and unbifid at the base.